PELAKSANAAN INVESTASI SEKTOR PARIWISATAPULAU-PULAU KECIL DI KABUPATEN PESISIR SELATAN - Koemala, Divya (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
Indonesia as a developing country is doing a lot of activities in Pesisir Selatan that is being actively growing. In this skripsi, the formulation of the problem are: a) how the government of Kab.Pesisir Selatan manage the investation in tourism of small islands. b) what is the government challange involved in investment in tourism of small Islands in Kab. Pesisir Selatan. Research methods used are juridical empirical, that is the existing approach with an understanding positif law of an object and how reality in the field. Then analyzed qualitatively and described descriptively. The results showed that: a) The basic investigation in Kab.Pessel has been implemented in accordance with UU Penanaman Modal and UU Kepariwisataan. In practice it finds one investment company and more than 12 domestic investors who invest in insland tourism. Activity that involved in investing in small islands tourism are tourist attraction transportation, tourism and travel agency, food and beverage, providing accommodatin and other tourism bussiness activity. b) in the implementation there is obstacles such as: whether unregistered land, potential investors who do not meet the requirements, lack of people awareness about investation commonly in tourism field, and low in facility in Pesisir Selatan. The government's ongoing solution is to counseling and coaching local communities to register their land, take care of permits and be open to investing activities and tourism, make it easier permit service and non permit service and coordinating inter-sectoral services to improve facilities.